Variation of DNA Repair Genes APE1 and RAD18 in β-Thalassemia Patients - Nawras Najah Jawad; Mona N. Al-Terehi (Medical Journal of Babylon)
Background: In the last decade, beta-thalassemia (β-thalassemia) has been recorded in high percentages among the Iraqi population and this disorder has a deficiency in β-globin chains causing striking heterogeneity of molecular disorder. The study subjects’ characteristics showed nonsignificant differences between age, body mass index, and the percentage of gender between patients and control. Objectives: The objective of the study was to detect the apurinic/apyrimidinic endonuclease enzyme (APE1) Asp148Glu (rs3136820) and RAD18 Arg302Gln (rs373572) in β-thalassemia patients. Materials and Methods: A case–control study was conducted, which included β-thalassemia patients. Thirty acute myeloid leukemia patients attended the Hematology Consultation Clinic and were diagnosed by a specialized hematologist belonging to disease criteria. The control group included 28 healthy individuals, blood samples were collected with approval from each contributor, and ethical approval was given according to the Ministry of Environment and Health in Iraq. Results: A significant elevation in iron and ferritin level were observed in the patient group (P = 0.000) the RAD18 genotypes showed nonsignificant differences between Gln/Gln and other genotypes, and between Gln/Arg and Arg/Arg, in allele frequency, there was nonsignificant difference also, the Gln/Arg genotype frequent in slightly changes in patients and control group, Arg/Arg did not observe in the control group. The APE1 genotype showed that GG and TT were more frequent in patients compared with the control group, GT was more frequent in the control compared with the patient group, and all changes were nonsignificant. The allele frequency showed that the T was more frequent in the patient group with nonsignificant differences. Conclusion: From this study, we can conclude there was a nonsignificant association between APE1 and RAD18 at the single-nucleotide polymorphisms RAD18 Arg302Gln (rs373572) the APE1 Asp148Glu (rs3136820).